The Effect of the Problem Based Learning (PBL) Learning Model on the Motivation and Learning Outcomes of Class XI SMPN 1 Sreseh - Siti Munawaroh; Sri Utami; Sucipto Sucipto (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study aims to explore the factors that affect the effectiveness of Problem-Based Learning (PBL) in improving student learning outcomes. PBL is a learning method based on real problem solving that requires students to think critically and work collaboratively. Although PBL has been proven effective in a variety of contexts, its implementation in developing countries and in various disciplines still faces challenges. The factors tested in this study included student characteristics (such as motivation and critical thinking skills), facilitator quality, environmental support (including educational facilities, technology, and policies), and subject matter characteristics. Through a literature analysis and case studies in several educational institutions, this study found that the effectiveness of PBL is highly dependent on the interaction between these factors. The characteristics of active and independent students, well-trained facilitators, and adequate environmental support can promote the achievement of better learning outcomes. Meanwhile, subject matter that is relevant and in accordance with the needs of students also plays a big role in the success of the implementation of PBL. This study provides recommendations for educators and policymakers to consider these factors in designing and implementing PBL in the educational environment.